Clonal Dissemination of Extended-Spectrum Cephalosporin-Resistant Enterobacterales between Dogs and Humans in Households and Animal Shelters of Romania - Andreea Paula Cozma; Cristina Mihaela Rimbu; Flavia Zendri; Iuliana Elena Maciuca; Dorina Timofte (MDPI AG, 2022)
Faecal carriage of extended-spectrum cephalosporin-resistant (ESC-R) Enterobacterales in healthy pets is a concerning issue. This study aimed to determine the prevalence, genetic background, and potential for interspecies transmission of these bacteria between dogs and humans within the same household (HH) or shelter environment in Romania. Faecal samples (n = 263) collected from healthy dogs (n = 102), their owners (n = 32), as well as dogs (n = 110) and staff (n = 19) from dog shelters, were screened for ESC-R carriage. Clonal relatedness of canine and human Escherichia coli isolates was established using Fourier Transform Infrared Spectroscopy (FTIR), followed by Illumina WGS of selected isolates. The highest prevalence of ESC-R Enterobacterales faecal carriage was identified in staff working at dog shelters (78.9%), followed by dogs from households (44.11%), dog owners (43.7%), and dogs from shelters (27%). FTIR identified 15 clusters of closely related E. coli isolates, including dog and human isolates from the same environment. Co-carriage of ESC-R isolates in both the dog and owner was identified in 12 HHs (37.5%), with two HHs (6%) having both the owner and dog carrying isolates with identical FTIR spectra, phylogroup, resistance genes, and Inc plasmids. Major ExPEC lineages such as ST127, ST10, ST155, and ST88 were detected in human and dog isolates. Our study revealed a high prevalence of faecal ESC-R E. coli carriage in both dogs and humans from Romanian households and shelters, where bidirectional clonal transmission between humans and dogs is likely. Furthermore, we identified ESC-R Enterobacterales co-carriage in people and dogs sharing the same environment using FTIR, demonstrating its value in AMR surveillance for humans and animals.